Comparative analysis of the discriminatory performance of different well-known risk assessment scores for extended hepatectomy - Ghamarnejad, Omid; Khajeh, Elias; Rezaei, Nahid; Afshari, Khashayar; Adelian, Ali; Nikdad, Mohammadsadegh; Hoffmann, Katrin; Mehrabi, Arianeb (Scientific reports, 2020)
The aim of this study was to assess and compare the discriminatory performance of well-known risk assessment scores in predicting mortality risk after extended hepatectomy (EH). A series of 250 patients who underwent EH (≥5 segments resection) were evaluated. Aspartate aminotransferase-to-platelet ratio index (APRI), albumin to bilirubin (ALBI) grade, predictive score developed by Breitenstein et al., liver fibrosis (FIB-4) index, and Heidelberg reference lines charting were used to compute cut-off values, and the sensitivity and specificity of each risk assessment score for predicting mortality were also calculated. Major morbidity and 90-day mortality after EH increased with increasing risk scores. APRI (86%), ALBI (86%), Heidelberg score (81%), and FIB-4 index (79%) had the highest sensitivity for 90-day mortality. However, only the FIB-4 index and Heidelberg score had an acceptable specificity (70% and 65%, respectively). A two-stage risk assessment strategy (Heidelberg-FIB-4 model) with a sensitivity of 70% and a specificity 86% for 90-day mortality was proposed. There is no single specific risk assessment score for patients who undergo EH. A two-stage screening strategy using Heidelberg score and FIB-4 index was proposed to predict mortality after major liver resection.